Diagnosis of plasma parameters for several ion engine samples in vacuum - Hayder Ridha Ali; Waleed Ibrahim Yaseen (AIP Advances)
Electric propulsion systems for ion engines used in satellites are promising technologies in the space field. To choose the optimal geometric shape for achieving high-intensity plasma, we conducted measurements and tests on several laboratory-made models. The measurements were taken inside a vacuum system to simulate the conditions of outer space. The plasma parameters, including the electron temperature, Debye radius, and electron density of the plasma, were calculated using a single Langmuir probe to diagnose plasma parameters generated inside the four models of ion engines used with a change in the DC power from 10 to 50 W under low pressure in the vacuum chamber of about 0.2 mbar. It was observed that the temperature decreases with increasing power for all ion engine sizes used. While the density increases with increasing power for all sizes used, the electron frequency of the plasma increases with increasing power. While the Debye radius is lower with increasing power for all sizes used, the engine size had a positive effect on the electron temperature and a negative effect on the electron density. The results showed that the optimal geometric shape is a triangular engine with a volume of 54 cm3 (T 5 × 5).